TIJORAT BANKLARI OMONATLARI HAJMINI OSHIRISHDA MIJOZGA YOʻNALTIRILGAN MARKETING STRATEGIYALARINI ISHLAB CHIQISH (Marketing Journal, 2026)
AbstractThe study examined customer-oriented marketing strategies aimed at expandingthe deposit portfolio of commercial banks from both theoretical and practicalperspectives. The impact of customer segmentation, personalized service delivery, anddigital marketing tools on deposit volumes in the banking sector was analyzed. Thedeposit dynamics of Uzbekistanʼs commercial banks during 2019-2024 were assessedbased on quantitative indicators. The research findings demonstrated that adifferentiated marketing approach grounded in thorough analysis of customer needs significantly enhanced deposit mobilization efficiency. Practical recommendationswere developed for implementing CRM systems, expanding financial literacyprograms, and diversifying digital channels.Keywords: deposits, commercial banks, marketing strategy, customerorientation, CRM, digital marketing, banking services, financial literacy